Arctigenin Induces an Activation Response in Porcine Alveolar Macrophage Through TLR6-NOX2-MAPKs Signaling Pathway - Lu, Zheng; Chang, Lingling; Du, Qian; Huang, Yong; Zhang, Xiujuan; Wu, Xingchen; Zhang, Jie; Li, Ruizhen; Zhang, Zelin; Zhang, Wenlong; Zhao, Xiaomin; Tong, Dewen (Frontiers in Pharmacology, 2018)
Arctigenin (ARG), one of the most active ingredients abstracted from seeds of Arctium lappa L., has been proved to exert promising biological activities such as immunomodulatory, anti-viral, and anti-cancer etc. However, the mechanism behind its immunomodulatory function still remains elusive to be further investigated. In this study, we found that ARG had no significant effects on the cell proliferation in both porcine alveolar macrophage cell line (3D4/21) and primary porcine derived alveolar macrophage. It remarkably increased the expression and secretion of the two cytokines including tumor necrosis factor-alpha (TNF-α) and transforming growth factor beta1 (TGF-β1) in a dose-dependent manner with the concomitant enhancement of phagocytosis, which are the indicators of macrophage activation. ARG also elevated the intracellular ROS production by activating NOX2-based NADPH oxidase. Furthermore, inhibition of ROS generation by diphenyliodonium and apocynin significantly suppressed ARG-induced cytokine secretion and phagocytosis increase, indicating the requirement of ROS for the porcine alveolar macrophage activation. In addition, TLR6-My88 excitation, p38 MAPK and ERK1/2 phosphorylation were all involved in the process. As blocking TLR6 receptor dramatically attenuated the NOX2 oxidase activation, cytokine secretion and phagocytosis increase. Inhibiting ROS generation almost abolished p38 and ERK1/2 phosphorylation, and the cytokine secretion could also be remarkably reduced by p38 and ERK1/2 inhibitors (SB203580 and UO126). Our finding gave a new insight of understanding that ARG could improve the immune-function of porcine alveolar macrophages through TLR6-NOX2 oxidase-MAPKs signaling pathway.